ANALISIS KEMAMPUAN GOOD CORPORATE GOVERNANCE DALAM MEMEDIASI PENGARUH VARIABEL KINERJA KEUANGAN, KINERJA LINGKUNGAN, DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN LINGKUNGAN - Fatikhatun Khasanah; Eliada Herwiyanti; Mafudi * (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2022)
This research is a literature study by analyzing the annual reports of PROPER participating companies listed on the Indonesia Stock Exchange in 2016-2017. This study aims to determine the ability of Good Corporate Governance to mediate the effects of financial performance, environmental performance, and company size on environmental disclosure.. The population in this study are all of PROPER participating companies that are listed on the Indonesia Stock Exchange during 2016-2017. Determination of samples using purposive sampling technique, so the number of samples is 32 companies. The results of this research show that: (1) Good Corporate Governance is able to mediate the effects of financial performance, environmental performance, and company size on environmental disclosure; (2) Good Corporate Governance is not able to mediate the effect of financial performance on environmental disclosure; (3) Good Corporate Governance is not able to mediate the effect of environmental performance on environmental disclosure; (4) Good Corporate Governance is able to mediate the effect of company size on environmental disclosure; (5) Financial performance has a positive but not significant effect on environmental disclosure; (6) Environmental performance has a positive but not significant effect on environmental disclosure; (7) Firm size has a positive and significant effect on environmental disclosure.